Sodium alginate microspheres loaded with Quercetin/Mg nanoparticles as novel drug delivery systems for osteoarthritis therapy - Jun Chen; Guoya Wu; Jian Wu; Zhijian Jiao (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteoarthritis (OA) is the most prevalent arthritic disease characterized by cartilage degradation and low-grade inflammation, for which there remains a lack of efficacious therapeutic interventions. Notably, mitigating the impact of oxidative stress (OS) and inflammatory factors could help alleviate or hinder the advancement of OA. Given the benefits of both quercetin (Que) and Magnesium ion (Mg2+) in OA treatment, coupled with the structural properties of Que, we have innovatively developed the Que-Mg2+ nanoparticles (NPs), aiming to deliver both Que and Mg2+ simultaneously and achieve enhanced therapeutic outcomes for OA. Moreover, to avoid the adverse reactions linked to frequent injections, sodium alginate (SA) microspheres encapsulating Que-Mg2+ NPs (Que-Mg@SA) were designed to treat the H2O2-induced OA cell model. Methods Que-Mg@SA microspheres were synthesized using the ionotropic gelation technique, with calcium chloride acting as the cross-linking agent. Comprehensive characterization of the Que-Mg@SA was conducted through transmission electron microscope (TEM), dynamic light scattering (DLS), optical microscope, and scanning electron microscope (SEM), which provided detailed insights into their size, zeta potential, morphology, and micromorphology. Additionally, the microsphere swelling rate and Que release were evaluated. The biocompatibility of Que-Mg@SA microspheres, along with their impact on chondrocyte viability, were detected through CCK-8 assay and live/dead cell staining. Furthermore, the antioxidant and anti-inflammatory properties of Que-Mg@SA were evaluated by examining the ROS scavenging ability and pro-inflammatory factors levels, respectively. Finally, the regulatory influence of Que-Mg@SA microspheres on extracellular matrix (ECM) metabolism in OA was assessed by immunofluorescence staining and Western blot. Results Characterization results revealed that Que-Mg NPs exhibit nanoscale diameter, exceptional stability, and good dispersibility, while Que-Mg@SA possesses high entrapment efficiency (EE%) and loading efficiency (LE%), pronounced hygroscopic properties, and sustained drug-release capabilities. Additionally, in vitro cellular assays revealed that the biocompatible Que-Mg@SA microspheres significantly restored chondrocyte viability, scavenged H2O2-induced excessive ROS, reduced the levels of inflammatory cytokines, upregulated cartilage anabolic gene expression, downregulated cartilage catabolic protease gene expression, and maintained the metabolic balance of cartilage tissue. Conclusion The functionalized Que-Mg@SA microspheres developed in our study hold great promise as a drug delivery system for OA and potentially other biomedical applications. Clinical trial number Not applicable. Graphical abstract